Kurikulum Merdeka dalam Perspektif Pedagogik - Syahrul Hamdi; Cepi Triatna; Nurdin Nurdin (SAP (Susunan Artikel Pendidikan), 2022)
Improving and equalizing the quality of education has been a major challenge to the government for a long time in developing education in Indonesia. The government continues to make improvements through various systematic steps, one of which is improvement in the curriculum by presenting an independent curriculum. This curriculum is expected to be the answer to the problem of the low basic literacy ability of students and will be fully implemented at all school levels in 2024. The curriculum alternation causes teachers to adjust their competencies, especially pedagogic competencies. Through a literature review research method conducted in 2022, researchers identified what pedagogical abilities need to be improved by teachers in optimally implementing the independent curriculum. The results of the study indicates that the pedagogic abilities that need to be improved by teachers include understanding constructivism learning theory, the ability to develop and determine approaches for the Pancasila student profile project and the use of expanded formative assessment in learning assessment.